Resistencia del ionómero de vidrio de restauración de autocurado odontológico a fuerzas de compresión. Universidad Nacional De Chimborazo, 2018 - Sibambe Guaño, Marco Vinicio (2019)
The different biomaterials that are used for the various dental treatments have evolved improving their different properties, especially their resistance. This is the case of glass ionomers which are modified in their composition with different byproducts thus improving their qualities and increasing their resistance in dental restorations facilitating to the professional the use of other alternatives in materials for restoration. The objective of the research work was to identify which glass ionomer preparation is the most resistant to the compressive forces application in simulated environments. The research was observational, descriptive, comparative, transversal and invitro. Compression tests were applied in 30 samples divided into 10 ionomer discs of three trademarks (Ketar Molar, Ionofil, Fuji). A set of samples was prepared with the manufacturer's dosage under saliva artificial conditions and other samples in which the liquid dosage was increased. In the multiple comparisons table, it was determined that there are significant differences among the resistance to compression forces (p = 0.022) or at least one was different so it was shown that the most resistant ionomer was the Fuji IX glass ionomer, with a value of its average of 38.57 MPa and a maximum resistance of 65,81Mpa.